Phosphorylated mixed lineage kinase domain‐like protein in human seminal plasma: A potential novel biomarker of spermatogenic function. (16th May 2019) - Xie, Yun; Lv, Linyan; Yao, Jiahui; Zhang, Chi; Chen, Haicheng; Chen, Wenqiu; Liang, Xiaoyan; Sun, Xiangzhou; Deng, Chunhua; Liu, Guihua
Abstract: Keeping the self‐renewal and differentiation of spermatogonial stem cell (SSC) in balance is essential for maintaining spermatogenesis. However, whether the cell death of SSC also plays a vital role in the human being remains unknown. To explore the necroptosis of SSC, the activation marker of necroptosis, phosphorylated mixed lineage kinase domain‐like protein (pMLKL) in testes was evaluated by immunofluorescence staining and Western blot. Meanwhile, a total of 81 semen samples were divided based on the sperm concentration (>15, 10–15, 5–10 and 0–5 million/ml) to study the relationships between pMLKL levels and sperm counts. We found that the pMLKL was increased in the ageing human testes ( p < 0.05). Moreover, the seminal pMLKL expression was decreased in groups with sperm concentration 0–5 and 5–10 million/ml when compared with normal sperm concentration in young men ( p < 0.05). Further analysis revealed that pMLKL showed an age‐related increased expression in men aged 22–60 years with normal sperm concentration. These data demonstrated that the necroptosis of SSC was important for the spermatogenic function and would raise in advance on the point of testicular hypofunction. In conclusion, the pMLKL may serve as a potential biologically seminal indicator for the spermatogenic function in men.